Manufacturing and bending behaviour of in situ foam-filled aluminium alloy tubes. (5th February 2015) - Duarte, Isabel; Vesenjak, Matej; Krstulović-Opara, Lovre; Anžel, Ivan; Ferreira, José M.F.
Graphical abstract: Highlights: Production of the in situ foam filled tube based on Al-alloys. Bending behaviour of in situ and ex situ foam filled tubes. Mechanical interlocking is significant for enhancing mechanical reliability. Predictable and superior mechanical properties have been achieved. Abstract: The manuscript focuses on manufacturing of new in situ foam-filled tubes ( in situ FFTs) of Al-alloys including the foaming stage and studying their mechanical behaviour under quasi-static and dynamic bending loadings. The composite structures were manufactured by the powder compact foaming technique. These structures are fabricated by heating foamable precursor material pieces above their solid temperature inside thin-walled tubes. Different manufacturing parameters were appropriately adjusted based on preliminary experiments. The mechanical crushing behaviour and failure mechanisms were assessed by three-point bending experiments supported by infrared thermography. The bending performance of in situ FFTs and ex situ foam-filled heat treated tubes ( ex situ FFTTs) were compared with that of empty tubes subjected to heat treatment. The observed results have been explained in terms of the structural changes in the thermally treated tubes, the surface roughness derived from oxidation, and the dimensions of the interface gap between the two components in the composite structures. The in situ FFTs composite structures confirmed stable and controllable deformation and a promising energy absorption capability.